Alois Rašín, Československo a moc ustavující - Ondřej Preuss (Právněhistorické studie)
The article discusses the concept of constituent and constituted power in the context of the establishment of the Czechoslovak state in 1918 – the constitutional revolution, with a particular focus on the role of Alois Rašín, a key figure in this process of discontinuity from the existing regime. However, the distinction between constituent and constituted power fails to explain how a new legal order arises without overly idealizing the constituent power. Author suggests focusing on specific values, such as democracy, political rights guarantees, and equality, rather than on the ephemeral nature of power during the creation of a new regime.